Authoring: An Essay for the English Profession on Potentiality and Singularity - JANIS HASWELL, RICHARD HASWELL (University Press of Colorado, Utah State Univer, 2010)
In information science, when input is known and output is known but the process that connects the two remains unknown, the situation is called a black box. This essay opens some black boxes safeguarded by the higher-education project called â€œEnglish.â€ Education and black boxes, of course, are joined by symbiosis in every department and discipline. This is because it takes black boxes to learn about black boxes. Fixers routinely use computerized tools about which they care to know little in order to diagnose problemsâ€” is there radon in the basement?â€”about which they hope to learn more. Bruno Latour (1987) shows that even in the enlightened field of the hard sciences, questioning of unquestioned procedures always uncovers more unquestioned procedures, like a Russian doll with no end to the parade of inner dolls. Yet as fixers and working scientists will respond, black boxes have to be taken for granted to get on with the investigation. That is why black boxes abound and abide. They are ideational as well as material, and they come in all shapes and sizes, as atomic as intuitions, as nebulous as presuppositions. Some of the most encompassing are the stuff our Enlightenment-Romantic- Modern-Postmodern dreams have been made on: Faradayâ€™s ether, Kantâ€™s categories, Hegelâ€™s Geist, Hopkinsâ€™ inscape, Freudâ€™s libido, Bergsonâ€™s life force, Skinnerâ€™s mentalism, Derridaâ€™s presence. Every discipline has its black boxes it doesnâ€™t want to plumb because the work has to get done, and work would have to wait while the basement is being tested. Every discipline including English. Authoring, the human inner act of making texts, is the one term that most unites the four divisions of English studiesâ€”composition, literature, linguistics, and creative writing. Yet in English departments authoring is currently a remarkably black box. Akin to the behaviorist concept of mentalism, which can only be inferred through measurable stimulus and measurable response, authoringâ€”the inward act that triggers the outward act of writingâ€”may be the one concept in the toolkit of the English trade that teachers of writing and written discourse least question. Those of us in literature and composition have often scoffed at stimulus-response methodology. Yet we think continually of input in terms of cultural environment, ethnic given, academic site, and instructional activity, and we think continually of output in the form of text, learning, grades, and test results. What lies in between we bracket as authoring: the internal human process of turning background, experience, and imagination into something written. It is not so much the author who is dead as the act of authoring.